Medication multiple experiences of elderly patient with multiple chronic condition: A qualitative meta-synthesis - Guo Xin; Wang Yuanxing; Wu Jiaming; Hu Xue (PLoS ONE, 2025)
Purpose To determine the experience of medication multiple in elderly patients with multiple chronic condition by systematically reviewing, retrieving, and synthesizing data from qualitative studies. Methods Nine databases were systematically searched for relevant contributions from the time of construction until October 30, 2024. All qualitative studies in English and Chinese exploring the real-life experiences, feelings, etc, of medication multiple in elderly patients with multiple chronic condition were included. The Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ).Two independent reviewers selected the studies and assessed the quality of each study, and the included studies were inductively analysed and interpreted then reported as a meta‐synthesis. Results A total of 10 studies revealed 13 sub-themes and 4 descriptive themes:Difficulties and challenges in Polypharmacy, Multi-party support facilitates Polypharmacy in elderly patients with multiple chronic condition,Positive attitude towards taking medication. Conclusion The health outcomes of elderly patients with coexisting chronic diseases can be significantly impacted by polypharmacy difficulties and challenges as well as lower medication adherence.Increasing medicine knowledge among older patients with concomitant chronic diseases, bolstering medication-taking beliefs, and motivating family members to support the patient are all ways to improve medication adherence. [REGISTRATION: PROSPERO ID: CRD42024628547]